JURIDICAL ANALYSIS OF SYAHBANDAR'S RESPONSIBILITY IN REALIZING SAFETY SHIPPING (KSOP Class III Kijang Office Research Study) - Arifin, Fatahur; Respationo, M. Soerya; Simatupang, Bachtiar (RADJA PUBLIKA, 2022)
The purpose of this study is to find out and analyze the porter's duties in realizing shipping safety, the porter's responsibility in realizing shipping safety, as well as the factors that become obstacles and alternative solutions to the porter's responsibility in shipping safety at the Port Authority and Class III Kijang Port Authority office. This study uses Grand theory, namely the theory of legal protection by Satjipto Raharjo, middle theory using the rule of law theory by Wirjono Projadikoro and applied theory using the theory of the law of happiness (utilitarianism) by Jeremy Bentham. This study uses a descriptive analysis approach to provide an overview and describe the object of research based on the facts that exist chronologically and systematically by using secondary data to obtain conceptual conceptions of theories, opinions or thoughts that are related to the object under study. Data collection techniques are library research and interviews which are then analyzed descriptively so that in addition to being able to describe and reveal the legal basis, they can also provide solutions to the problems in question. The population in this study were all employees and leaders of the Class III Kijang Harbormaster and Port Authority Office, with a sample of 4 people who were randomly selected and considered to be able to describe the characteristics of the population. The results of the analysis concluded,